Ethical Issues in Arms Technology - Nwoye , Leonard (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
The paper Ethical Issues in Arms Technology is written to highlight and explain some ethical issues in arms production. These issues include the act of innovation; issues with weapons of mass destruction, the issue of privacy; humanizing arms technology, artificial intelligence – military killer robots, etc. The paper advocated for a critical evaluation of the structural and potential nature of arms before they are mass-produced. We need to ask and address all possible moral questions at the research level rather than wait for the technologies to be developed and sent to the market place. The research employed the methods of rational speculation, critical analysis, evaluation, and prescription to call for the ethical assessment of all arms before they are made available to the markets. This paper advocate for a stop on the production of any arms technology that will destroy the relationship between man and his environment. Scientists and arms researchers should give ethics a stool at the heart of their research and production. Before production, every arms technology template must be ethically worthy before consideration is made to mass-produce them. With this new development, we shall eradicate the production of non-human value-adding arms from our world. Humanity does not need everything it produces. We should accept and produce only what we need.